Implementation of Project Based Learning Model to Develop Students' Creativity and Collaboration Skills in P5 - Rita Yuliyanti; Sintia Febriyanti; Agung Setyawan (Penerbit Presisi Pustaka, 2025)
This study aims to analyze the implementation of Project-Based Learning (PjBL) as an innovative approach centered on real-world projects, in line with the Pancasila Student Profile Strengthening Project (P5) under the Merdeka Curriculum, to improve students' independence, creativity, problem-solving skills, and internalize Pancasila values ​​such as mutual cooperation, creativity, and environmental responsibility through project examples such as